Meanings Constructed by Academics About the Teaching of Linguistics for Teacher Training: A Case Study [Significados Construidos por Académicos Acerca de la Enseñanza de la Linguistic Para Profesores en Formación: Un Studio de Caso] - Rubio-Manriquez, M (Universidad Catolica Silva Henriquez, 2021)
This article describes the meanings constructed by university academics that study linguistics in regard to the teaching of the discipline to future L1 teachers. It refers to a qualitative case study that involved interviewing 11 academics who teach degrees in Spanish Pedagogy. The results indicate that the discourse of academics is distributed into two areas linked to the teaching of linguistics: A) a scientific knowledge valid in itself and b) the formation of an active subject aware of their discursive practices. The article concludes that there is an unaddressed tension between an applicationist vision of positivist roots versus a vision of didactic reworking of content based on a humanist approach. © 2021 Universidad Catolica Silva Henriquez. All rights reserved.